Transition Program in Malaysia: The Challenges for Students with Special Needs in the Workplace - Zainal, Mohd Syazwan; Yassin, Mohd Hanafi Mohd; Tahar, Mohd Mokhtar (Journal of ICSAR, 2019)
The transition of career begins with vocational skills training conducted in schools according to the capabilities special needs students. Then, the process goes on with a workplace training program. The transition program is able to provide students with special needs to improve their working skills as well as gain initial experience at the workplace. This case study was conducted on 5 Master of Special Education from Universiti Kebangsaan Malaysia. This student has implemented a career transition program for students with special needs in their respective areas. Semi-structural interviews were conducted using instruments constructed based on past studies. Findings show that there are various challenges faced by students with special needs while undergoing training at the workplace. Among the challenges face by students with special needs are  problem of adapting to the working environment, communication skills, difficulty to understand instruction, students’ attitude completing task, relationships at the workplace and perception towards special needs students. However, through this career transition program, it can provide students with special needs with the initial experience of work skills required at the workplace. This program is able to contribute to a better quality of life after completing their education at the school level.